Perancangan Boardgame Pemilahan Sampah pada Anak Usia 6-7 Tahun di SDN Penanggungan - Iqlimah Agustin; Restu Ismoyo Aji (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service focuses on designing educational learning with interactive board game media which is a teaching and learning activity, as well as providing board game board media which is designed in such a way as to convey messages and information in the form of waste sorting, thereby trying to improve the quality of learning and also entertainment media. By introducing the concept of environmental cleanliness based on Adiwiyata to children aged 6-7 years, especially for children who attend SDN Penanggungan. This was done because there is still no availability of board game interactive media learning education for children aged 6-7 years and the lack of media facilities and educational toys at Penanggungan Elementary School. This service method uses qualitative methods by collecting data including observations, interviews, focus group discussions and surveys. With the educational learning media interactive board game for sorting organic and inorganic waste, children can enjoy the learning process without having difficulty understanding the information presented and getting bored or bored, and by providing facilities in the form of interactive board media for selecting organic and inorganic waste such as educational toy board games that sharpen motor skills and increase focus on children at school. The results of this service show that this program can provide an understanding of environmental cleanliness regarding the organic and inorganic waste selection system and increase adequate facilities for practical learning activities at Penanggungan Elementary School.